Airborne microbial counts in the oral medicine section, University of the Philippines College of Dentistry - Manansala, Katrina M.; Puzon, Mical Ellaine; Sunico-Segara, Michelle (Manila Department of Community Dentistry, University of the Philippines Manila, 2015)
Methods: This study has a comparative and cross-sectional design. Passive sampling was done using 10 settle plates randomly distributed around the Oral Medicine Section for 3 rounds, 7 o'clock (at rest), 12 o'clock, and 4 o'clock (in operational). The collection was done following Fisher's schedule of 1/1/1, wherein the plates were placed 1 meter from the floor, 1 meter from the wall, and opened for 1 hour. The procedures done in the morning and afternoon on each dental unit were noted. After collection, the plates were incubated at 37°C for 48 hours. Non-parametric, Kruskal-Wallis test was used to determine the level of significance in the mean values of CFU counts among the three rounds. Pearson correlation test was used to evaluate the association between the CFU counts with the number of people, as well as the relationship of CFU counts with the procedures performed.
Results: Both rounds in operational (12 and 4 o'clock) showed significant difference than at rest (7 o'clock). According to suggested guidelines from previous studies, the CFU counts obtained at rest was within safe levels, however, CFU counts in operational at 4 o'clock was beyond the acceptable limit. There was a greater attendance in the morning, however, the CFU was higher in the afternoon. Ultrasonic scaling, endodontic access preparations, and manual endodontic treatment showed a high positive correlation with the CFU production, while manual scaling revealed a medium correlation. Individual correlation of the plates and the procedures on approximating chairs was done, and majority showed ultrasonic scaling procedures produced greater microbial aerosols.
Conclusion: According to the guidelines established by previous studies, the amount of airborne microbial contamination in the OM Section was under the acceptable air microbial index at rest, but beyond acceptable levels during high activity.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila
Keywords: Air--Microbiology.; Aerosol; Microbial contamination; Bacteria